Reconceptualising Preservice Teachers’ Subject Knowledge in Climate Change and Sustainability Education: A Framework for Initial Teacher Education from England, UK - Majid, Nasreen; Marston, Sarah; Reed Johnson, Jo Anna; Happle, Andrew (Sustainability, 2023)
Climate Change and Sustainability Education (CCSE) has been gaining prominence with the imminent climate emergency humanity is facing. This paper draws upon a conceptual framework created to support the development of preservice teachers’ subject knowledge of CCSE whilst undertaking Initial Teacher Education (ITE) programs in England. The core aims and learning outcomes within the framework, namely knowledge; attitudes, values and behaviours; and competences and capabilities, are defined to illustrate what subject knowledge looks like, in this area, for preservice teachers in England. This paper highlights data gathered from 71 preservice teachers via an initial presurvey from three ITE institutions across England. The data were gathered from Early Years and Primary and Secondary phase trainees across both postgraduate and undergraduate programmes. The presurvey captured a range of qualitative and quantitative responses from preservice teachers to showcase priority areas, from their perspective, in the teaching of CCSE. The responses were coded and then themed according to the three aims and learning outcomes of the framework (knowledge; attitudes, values and behaviours; and competences and capabilities) to understand preservice teachers’ views on CCSE at the start of their courses. The findings suggest that preservice teachers lack key subject knowledge in CCSE to teach it effectively in schools. Hence, this paper recommends further work needs to be carried out to embed CCSE work in ITE courses across England. It is further suggested that the CCSE framework highlighted in this paper can act as a key national document to support ITE institutions to conceptualise the teaching and learning of CCSE across their ITE programmes.